A Historical Perspective of Christians: a Study on Socio Political Improvement and Indian National Movement: Exploring the Role of Indigenous Christianity in the Indian National Movement (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Indiagained Independencefrom the British colonial power sixty years ago. Her achievement of Independence was a resultof about a century's struggle by the people. The struggle for freedom was notan involvement of few people but rather it was a people's movement where everysection of people played their roles. The Indian national movement has a longhistory. As a matter of fact, it began with the Revolt of 1857. The Revolt had.been called as Sepoy Mutiny, by the British people, but many Indians consideredit as the first war of India's Indepertdence.1 However, the actual struggle forfreedom began with the formation of the Indian National Congress (INC) in 1885.The period between the Revolt of 1857 till the formation of the INC in 1885 wasmarked by a rapid growth of National consciousness for political freedom. Withthe formation of INC the Nation~ struggle became an organized movement. This paper will focus on new Christian movementsindigenous to Indiamost of which are not well known to outsiders but are active, contextual andvibrant in witness. Indigenous Christianity which had significant growth in thetwentieth century has roots in earlier attempts in Bengal, Tamil Nadu and Maharashtra. It includes the National Missionary Societyand numerous other Indian initiatives. Asian incarnations of the gospel arefound in historic as well as non-traditional Churches of several countries, butespecially in India.Some of the independent Churches are perceived as deviant in theology orcharacterized by folk religious practices. Through their worship, practice andteaching many independent Churches respond to the day to day experience andgrass-roots culture of the people. Theirs is a vigorous expression of Christianfaith and witness of the Spirit in Asia today.